In silico prediction of the metabolism of Blastocrithidia nonstop, a trypanosomatid with non-canonical genetic code - Opperdoes, Fred R; Záhonová, Kristína; Škodová-Sveráková, Ingrid; Bučková, Barbora; Chmelová, Ľubomíra; Lukeš, Julius; Yurchenko, Vyacheslav (BMC genomics, 2024)
BACKGROUND: Almost all extant organisms use the same, so-called canonical, genetic code with departures from it being very rare. Even more exceptional are the instances when a eukaryote with non-canonical code can be easily cultivated and has its whole genome and transcriptome sequenced. This is the case of Blastocrithidia nonstop, a trypanosomatid flagellate that reassigned all three stop codons to encode amino acids. RESULTS: We in silico predicted the metabolism of B. nonstop and compared it with that of the well-studied human parasites Trypanosoma brucei and Leishmania major. The mapped mitochondrial, glycosomal and cytosolic metabolism contains all typical features of these diverse and important parasites. We also provided experimental validation for some of the predicted observations, concerning, specifically presence of glycosomes, cellular respiration, and assembly of the respiratory complexes. CONCLUSIONS: In an unusual comparison of metabolism between a parasitic protist with a massively altered genetic code and its close relatives that rely on a canonical code we showed that the dramatic differences on the level of nucleic acids do not seem to be reflected in the metabolisms. Moreover, although the genome of B. nonstop is extremely AT-rich, we could not find any alterations of its pyrimidine synthesis pathway when compared to other trypanosomatids. Hence, we conclude that the dramatic alteration of the genetic code of B. nonstop has no significant repercussions on the metabolism of this flagellate.
Keywords: genetický kód; terminační kodon; Eukaryota; Non-canonical genetic code; In silico; Codon, Terminator; Blastocrithidia; Trypanosomatid; Trypanosomatina; paraziti; Animals; Parasites; zvířata; Metabolic predictions; Trypanosoma brucei brucei; Genetic Code